Efficiency and productivity of Indonesian Islamic Banking - Afiatun, Pipit; Wiryono, Sudarso Kaderi (Jurnal Manajemen Teknologi, 2010)
The direction of the Indonesian banking industry development policy based on the vision of achieving a healthy banking system, strong and efficient to create a stable financial system in order to drive national economic growth. Using analysis of efficiency and changes in Total Factor Productivity of the banking industry during the 2004 to 2009 period, this research aims to observe at the performance of Islamic banking as the new actors of Indonesian banking industry. To analyze the efficiency, this research utilize the method of non-parametric Data Envelopment Analysis (DEA). To measure changes in Total Factor Productivity of Islamic banking industry Malmquist Productivity Index is utilized. From the calculation of relative efficiency by means of input-oriented DEA and also the assumption of Variable Returns to Scale, the study indicated that the efficiency of Islamic banks in the 2004-2009 period are lower on the average compared to conventional banks; except during the period of July 2004 to December 2005. There are three Islamic banks analyzed for this particular research, namely Bank Muamalat, Bank Syariah Mandiri and Bank Syariah Mega, consecutively ranked 3rd, 10th, and 13th within the index of productivity. Yet, the results of t-test concluded that the efficiency and productivity of Islamic banks and conventional banks, statistically, are not significantly different. These results indicated that Islamic banking in general possess the ability to compete with conventional banking in Indonesia.Keywords: Indonesian Islamic Banking, DEA, Efficiency, Malmquist Index, Total Factor Productivity.